Development of Prototype System Design with The Application of Technology - Titi Ratnasari; Intan Ratna Sari Yanti; Dwi Anggaini (CV ODIS, 2022)
The development of a system designed in such a way as to become security that makes everyone feel the need to ensure the safety of everything that includes himself, both from his activities and the assets he owns. This system uses an RFID Reader with a frequency of 13.56 MHz and an ATMega328 Microcontroller that acts as a controller or circuit controller and is tested with hardware and software testing to determine the performance between the software and hardware of the device. This research shows that the RFID Reader can detect E-KTP with a maximum distance of 2.5 cm, and the solenoid will lock back after 3 seconds. The utilization of Renewable Energy is currently a priority in carrying out technology development, one of which is solar energy with solar panels as electrical energy. This research supports efforts to develop energy-based technology that is converted with various supporting components and system authentication designed using the use of control security systems both in terms of administration and information technology-based on population data and uncontrolled system prototypes.